Water Quality Analysis on Tertiary Channels Using Macroinvertebrate In Songka Sub-District, Palopo City - Abdul Rais; Aminudin Afandhi; Budi Prasetya (Indonesian Journal of Environment and Sustainable Development, 2019)
Changes in the condition of aquatic environment are now a major problem for the survival of every organism caused by changes in land use, human activities, and agriculture. This study aims to determine the structure of macroinvertebrate communities. In addition, this study also aims to conduct analysis on BMWP index and water quality testing using physical and chemical parameters. This study was conducted on tertiary channels in Songka Sub-District, Palopo City. Each station's data collection covered relative density, macroinvertebrates that were found were assessed using BMWP index, then they were calculated using ASPT index. The results of this study found 17 taxa classified in the class of gastropods, insecta, bivalvia, malacostraca, citellata, oligochaeta and hirudenia. The results of BMWP index modification analysis from all stations found that ASPT value was “quite-poor” and “bad”. It was indicated that in each station was mainly dominated by Oligochaeta worms and tolerant macroinvertebrates. Testing of physical and chemical parameters obtained DO value which belonged to class II of water quality. The low DO value caused high BOD value, which was classified in class III. The high value of BOD had an effect on the rise of COD value, the increase of COD value was caused by the high amount of organic and inorganic materials entering the water. PH value was relatively normal with the range of 6.3 to 6.8, temperature was in the range of 27.1°C to 28°C, the rise in temperature value was influenced by tree shade and the intensity of sunlight.Keywords: BMWP-ASPT, Community structure, Macroinvertebrate, Pollution, Tertiary channel